2013
DOI: 10.1017/s0033291713001037
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a consistent pattern of neural function in attention deficit hyperactivity disorder: a meta-analysis

Abstract: Consistent frontal deficits imply homogeneous cognitive strategies involved in ADHD behavioural control. Our findings suggest a link between fMRI results and the potentially normalizing effect of treatment and signify a need for segregated examination and contrast of differences in sample characteristics in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
124
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 67 publications
21
124
0
Order By: Relevance
“…The imaging results of this study are largely in line with the meta-analysis of McCarthy et al (2014) and Hart et al (2013), showing reduced activation in rIFG/insula and dmPFC areas. The rIFG is part of a putative inhibition network, connected via a direct pathway with the subthalamic nucleus (STN), both of which are connected with the pre-SMA (Aron, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The imaging results of this study are largely in line with the meta-analysis of McCarthy et al (2014) and Hart et al (2013), showing reduced activation in rIFG/insula and dmPFC areas. The rIFG is part of a putative inhibition network, connected via a direct pathway with the subthalamic nucleus (STN), both of which are connected with the pre-SMA (Aron, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…A recent meta-analysis (McCarthy et al, 2014) of five stop task studies in children with ADHD showed reduced activation in bilateral IFG/Ins, right medial frontal gyrus, and right superior and middle frontal gyri. Partially overlapping results were found in another meta-analysis (Hart et al, 2013) of 15 studies using the stop task or go-nogo (GNG) tasks, with reduced activation for ADHD in the right IFG/Ins, right SMA and ACC, right thalamus, left caudate and right occipital cortex.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence from neuropsychological studies and functional brain imaging studies such as single-photon emission CT, functional MRI and positron emission tomography in individuals with ADHD have shown that neural activity is reduced in prefrontal cortex [3,6,35] . Interestingly, this area is involved in generation of autonomic tone and plays a vital role in higher order autonomic control [7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that right hemispheric dysfunction is most likely to result in the symptoms of ADHD [25,26]. In addition, several structural [27,28] and functional [29,30] brain imaging studies have also demonstrated smaller and less activated anterior regions in the right hemisphere. Even though many studies support the hypothesis of right hemispheric involvement in ADHD, other studies have reported opposite results or different opinions.…”
Section: Discussionmentioning
confidence: 99%